Bem Publico (1863)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Bem Publico (1863)
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage

Cours de Conferences Sur La Religion (Victor Palme, Libraire,, 1863)
Front Cover and Title Page Missing
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; 8.Tear; Condition: Poor; Paperback; Religion

Cours de Conferences Sur La Religion (Victor Palme, Libraire,, 1863)
Front Cover and Title Page Missing
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; 8.Tear; Condition: Poor; Paperback; Religion

MARCOLFO O MALOÏNO. (Imprensa de L. Correa da Cunha, 1863)
Ou mysterios da familia Loc-Ronan. Por. Tradução de J. M. d'Andrade.
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

MARCOLFO O MALOÏNO. (Imprensa de L. Correa da Cunha, 1863)
Ou mysterios da familia Loc-Ronan. Por. Tradução de J. M. d'Andrade.
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

MARCOLFO O MALOÏNO. (Imprensa de L. Correa da Cunha, 1863)
Ou mysterios da familia Loc-Ronan. Por. Tradução de J. M. d'Andrade.
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

MARCOLFO O MALOÏNO. (Imprensa de L. Correa da Cunha, 1863)
Ou mysterios da familia Loc-Ronan. Por. Tradução de J. M. d'Andrade.
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Hard Cover; Literature

Mois de Marie (Libraire de Mme Ve. Poussielgue-Rusand, 1863)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Mois de Marie (Libraire de Mme Ve. Poussielgue-Rusand, 1863)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O Instituto, Jornal Scientifico e Litterario (Imprensa da Universidade, 1863)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

O Instituto, Jornal Scientifico e Litterario (Imprensa da Universidade, 1863)
Keywords: 1.Conservation 保護; 10.Cover Damage; 18.Bookworm; 2.Damage

Question de Soeurs de La Charite en Portugal, 1857-1862 (Imp. de la Societe Typographique Franico-Portugaise, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Question de Soeurs de La Charite en Portugal, 1857-1862 (Imp. de la Societe Typographique Franico-Portugaise, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Sancti Caroli Borromaei Orationes XII (1863)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

Sancti Caroli Borromaei Orationes XII (1863)
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm

camoes pelo visconde de almeida-garrett - Almeida Garrett (em casa da viuva bertrand e filhos, 1863)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

romanceiro pelo visconde de almeida-garrett vol 3 romances cavalherescos antigos - Almeida Garrett (Em casa da viuva Bertrand e filhos, 1863)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

romanceiro pelo visconde de almeida-garrett vol.1 romances da renascenca - Almeida Garrett (em casa da viuva bertrand e filhos, 1863)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

theatro do visconde de almeida-garrett vol6 o alfageme de santarem - Almeida Garrett (Imprensa Nacional, 1863)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

Romanceiro pelo visconde de almeida-garrett vol.2 romances cavalherescos antigos - Almeida Garrett, João Baptista da Silva Leitão de Almeida Garrett (Em casa da viuva Bertrand e filhos, 1863)
Keywords: 18.Bookworm; Condition: Fair; Hard Cover; Literature

Quadros historicos de Goa: tentativa historica - Barreto de Miranda, Jacinto Caetano (Na Typ. do Ultramar, 1863)
OCLC: 29055569
Keywords: 16.Waterstains; 18.Bookworm (Only Cover); Condition: Fair; Goa; Daman and Diu (India) History; Hard Cover; History; India; India Goa; Daman and Diu; Portugais Inde; Portuguese; Portuguese India

Maravilhas do genio do homem descobrimentos e invenções, descripções historicas divertidas e instructivas sobre a origem e.. - Bast, Amédée de; Magalhães, Matheus Luiz Coelho de; Silva, Innocencio Francisco da (José Maria Correa Seabra, 1863)
OCLC: 77544890
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; Condition: Fair; History; Invenções; Paperback

Curso elementar de physica - Benevides, Francisco de Fonseca (IMPRESA NACIONAL, 1863)
OCLC: 48168079
Keywords: Chemistry; Chimie; Condition: Fair; Paperback; Physics; Physique; Teaching; chemistry; physics

La maison de glace, ou, Le chasseur de Vincennes - Bresciani, Antonio (Casterman, 1863)
Cover Lost
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 22.signature; Condition: Fair; Hard Cover

La moralizadora y salvadora del mundo es la confesión sacramental (Librería Religiosa, 1863)
Texto en castellano, notas en latín
OCLC: 1151587103
Keywords: 10.Cover Damage; 18.Bookworm (Only Cover); 2.Damage; Condition: Fair; Hard Cover; Libros; Penitencia

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Histoire Generale des Auteurs Sacres et Ecclesiastiques - Ceillier, R. P. Dom Remy (Chez Louis Vives, Libraire- Editeur, 1863)
Keywords: 1.Conservation 保護; 18.Bookworm; 2.Damage

Reflexões sobre a lingua portugueza: Publicadas com algumas annotações pela Sociedade propagadora dos conhecimetnos uteis - Freire, Francisco José (Typographia do Panorama, 1863)
OCLC: 793580820
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair; Portugais (Langue); Portugais (Langue) Grammaire; Portuguese language; Portuguese language Grammar; languages

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1863)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1863)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

Bullarum Diplomatum et Privilegiorum Sanctorum Romanorum Pontificum Taurinensis Editio - Gaude, Francisco (Seb. Franco, et Henrico Dalmazzo Editoribus, 1863)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 18.Bookworm; 2.Damage

La Moralizadora y Salvadora del Mundo es La Confesion Sacramental - Gual, Pedro (Libreria Religiosa, 1863)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

La Moralizadora y Salvadora del Mundo es La Confesion Sacramental - Gual, Pedro (Libreria Religiosa, 1863)
Stamp of St. Joseph Seminary
Keywords: 1.Conservation 保護; 15.Stain 污漬; 2.Damage

Analyse da carta Constitucional da monarchia portugueza, decretada, e dada por D. Pedro imperador do Brazil aos 29 d'Abril de 1826, nos artigos que tocam em religião - Jesus, António de (Typ. União, 1863)
OCLC: 958972445
Keywords: 10.Cover Damage; 2.Damage; Condition: Fair

Viagem da corveta dom João I á capital do Japão no anno de 1860 - Marques Pereira, Feliciano Antonio (Imprensa Nacional, 1863)
with Map
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 21.Attachment; Condition: Poor; Hard Cover; History; Travel

Carmina Selecta - Nozzi, Henrici (Typ. Morini, 1863)
OCLC: 955482944
Keywords: 18.Bookworm; 2.Damage; Condition: Fair; Hard Cover

Concordanza delle scienze naturali: e principalmente della geologia con la Genesi fondata sopra le opinioni dei santi padri e di altri distini teologi - Saldanha, João Carlos de Saldanha de Oliveira e Daun (Tipografia Salviucci, 1863)
OCLC: 234176742
Keywords: 10.Cover Damage; 18.Bookworm; 2.Damage; 8.Tear; Bible and science; Bible et sciences; Condition: Poor; Paperback; Religion and science; Religion et sciences; natural sciences